Method for inducing high-hardness and high-wear-resistance gradient structure 60NiTi alloy through laser quenching
The gradient structure of 60NiTi alloy is constructed through laser quenching, which solves the problem of high hardness but poor impact resistance after high temperature solution treatment, and achieves a combination of high surface hardness and high wear resistance, maintaining the super elastic properties of the alloy.
Patent Information
- Application Number
- CN202411288255.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-14
- Publication Date
- 2024-12-17
- Estimated Expiration
- 2044-09-14
AI Technical Summary
60NiTi alloy has high hardness but poor impact resistance after high temperature solution treatment, low hardness and poor wear resistance in the medium temperature aging state, making it difficult to have both high wear resistance and high impact resistance.
The surface of the 60NiTi alloy with medium temperature aging is treated by laser quenching to build a gradient structure. The interior is dominated by TiNi phase and Ni3Ti phase, and the surface is dominated by Ni4Ti3 phase and TiNi phase. The nano-level Ni4Ti3 phase is formed by controlling the laser quenching temperature. Improve surface hardness and wear resistance.
While maintaining the super elastic properties of the alloy, the surface hardness and wear resistance are significantly improved, achieving a good combination of high wear resistance of the alloy surface layer and high stress impact resistance of the core.
Smart Images

Figure CN119144913A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of high-nickel NiTi alloy processing, and in particular to a method for inducing a high-hardness and high-wear-resistant gradient structure 60NiTi alloy by laser quenching. Background Art
[0002] With the rapid development of major mechanical equipment such as aerospace, maritime exploration and transportation in my country, the service environment of wear-resistant parts has become increasingly complex and harsh. Materials are often subjected to the coupling effects of alternating loads, vibration loads, high pressure, and corrosive environments, which puts higher requirements on the mechanical properties and friction and wear properties of materials. Bearings are an important component in mechanical equipment. Their main functions are to transfer loads, support mechanical rotating bodies, ensure rotation accuracy, and reduce the friction coefficient between mechanical parts. The quality of bearings directly determines the service life of the equipment.
[0003] 60NiTi (Ni content 60wt%, 55at%) alloy is an ordered intermetallic compound with CsCl type B2 cubic crystal structure. The covalent bond formed by the shared electron pair between Ti and Ni makes it have some ceramic properties and the elasticity and plasticity of metal materials, thus showing the characteristics of high hardness and low elastic modulus (about 100GPa). In addition, 60NiTi alloy has many advantages such as non-magnetic, corrosion resistance, and large recovery strain. Therefore, 60NiTi alloy has become a new type of high-end wear-resistant and corrosion-resistant material with great application potential. NASA has selected it as an alternative material for bearings in the urine recovery system of astronauts on the International Space Station.
[0004] After high-temperature solution treatment, the hardness of 60NiTi alloy can reach 645Hv, and it can obtain high hardness and high wear resistance. However, it is difficult to obtain good superelastic performance of 60NiTi alloy after high-temperature solution treatment, and its ability to resist local high-frequency stress impact is poor, which can easily cause component failure in vibration situations. Medium-temperature aged 60NiTi alloy shows good linear superelasticity, and can recover strain up to 5%, with good impact resistance, but its hardness is only 380Hv and its wear resistance is poor. How to make 60NiTi alloy have both high wear resistance and corrosion resistance and high impact stress resistance has become a technical problem that needs to be solved in this field. Summary of the invention
[0005] In view of this, the purpose of the present invention is to provide a method for inducing high hardness and high wear resistance gradient structure 60NiTi alloy by laser quenching. The present invention can obtain a surface ultra-high hardness layer while maintaining superelasticity, and achieve a good combination of high wear resistance of the alloy surface and high stress impact resistance of the alloy core.
[0006] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0007] The invention provides a method for inducing a high-hardness and high-wear-resistant gradient structure of a 60NiTi alloy by laser quenching, comprising the following steps: performing laser quenching on the surface of the 60NiTi alloy that has been subjected to medium-temperature aging treatment.
[0008] Preferably, the medium-temperature aging treatment is performed at a temperature of 800 to 900° C. and a holding time of 3 to 4 hours.
[0009] Preferably, the temperature of the laser quenching is 1000-1300°C.
[0010] Preferably, the temperature of the laser quenching is 1150-1250°C.
[0011] Preferably, the spot type of the laser quenching is flat top light, the spot length is 10 to 12 mm, and the spot width is 3.5 to 4.5 mm.
[0012] Preferably, the scanning rate of the laser quenching is 8-10 mm / s.
[0013] Preferably, during the laser quenching, a cooling water flow is used to cool the area scanned by the laser, and the cooling water flow is 20 to 30 mm away from the light spot.
[0014] Preferably, after each laser quenching is completed, the obtained sample is placed in cold water until the sample temperature drops to room temperature before the next laser quenching is performed.
[0015] The present invention provides a high-hardness and high-wear-resistant 60NiTi alloy, which is obtained by the method described in the above scheme; the hardness of the high-hardness and high-wear-resistant 60NiTi alloy decreases from the surface to the core; the interior is mainly composed of TiNi phase and Ni3Ti phase, and the surface is mainly composed of Ni4Ti3 phase and TiNi phase.
[0016] Preferably, the surface hardness is 400-650 Hv, and the average friction coefficient is 0.39-0.62.
[0017] The present invention provides a method for inducing a high-hardness and high-wear-resistant gradient structure of a 60NiTi alloy by laser quenching, comprising the following steps: laser quenching the surface of a 60NiTi alloy that has been subjected to medium-temperature aging treatment. The present invention uses laser quenching to perform surface treatment on a medium-temperature aged 60NiTi alloy, constructs a gradient structure, wherein the interior is mainly composed of TiNi phase and Ni3Ti phase, and the alloy maintains good superelasticity to withstand high stress overload impact, while the surface layer is mainly composed of Ni4Ti3 phase and TiNi phase, and high hardness and high wear resistance are obtained, thereby obtaining a surface ultra-high hardness layer while maintaining superelasticity, and achieving a good combination of high wear resistance of the alloy surface layer and high stress impact resistance of the alloy core. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] Figure 1 This is a schematic diagram of the structure of the equipment used for laser quenching;
[0019] Figure 2 This is the sample picture of 60NiTi alloy after laser quenching;
[0020] Figure 3 The XRD patterns of the surface of 60NiTi alloy before and after laser quenching; (a) 60NiTi matrix aged at medium temperature; (b) XRD patterns of the surface of samples with different laser quenching temperatures after removing the oxide scale;
[0021] Figure 4 Vickers hardness of the polished surface of 60NiTi alloy after laser quenching;
[0022] Figure 5 is the Vickers hardness of the cross section of the sample laser quenched at different temperatures;
[0023] Figure 6 is the friction coefficient curve of 60NiTi alloy after laser quenching treatment;
[0024] Figure 7 This is the superelastic stress-strain curve of the 60NiTi sample after high temperature quenching and medium temperature aging at room temperature and 30 cycles. DETAILED DESCRIPTION
[0025] The invention provides a method for inducing a high-hardness and high-wear-resistant gradient structure of a 60NiTi alloy by laser quenching, comprising the following steps: performing laser quenching on the surface of the 60NiTi alloy that has been subjected to medium-temperature aging treatment.
[0026] The present invention has no special requirements for the source of the 60NiTi alloy, and it can be prepared by commercial products or methods well known in the art. In the embodiment of the present invention, the 60NiTi alloy ingot is prepared by itself: 99.96% nickel and 99.8% titanium are selected as raw materials for alloy preparation, the surface of the metal raw materials is polished to remove the surface oxide scale, ultrasonic cleaning, and placed in a drying oven for drying; an electronic balance is used to weigh the titanium and nickel metals according to the mass percentage for standby use; a vacuum suspension furnace is used to melt the alloy, and the metal raw materials are placed in the melting crucible in the furnace in order from low to high melting points, and the sample chamber is evacuated to 5×10 -2 Pa is filled with high-purity argon for protection; the temperature is raised electrically to 1500°C to start melting, smelting for 15 minutes and then refining for 5 minutes, adjusting the power to cool down, repeating the smelting for 3 times, casting and cooling in the furnace to obtain the smelted 60NiTi alloy ingot.
[0027] In the present invention, the temperature of the medium-temperature aging treatment is preferably 800-900°C, and the holding time is preferably 3-4 hours; in a specific embodiment, the temperature of the medium-temperature aging treatment can be 800, 850 or 900°C, and the holding time can be 3, 3.5 or 4 hours. In the present invention, the medium-temperature aging treatment is preferably carried out in a muffle furnace. The cooling method of the medium-temperature aging treatment is preferably cooling to room temperature with the furnace.
[0028] In the present invention, the temperature of the laser quenching is preferably 1000-1300°C. In a specific embodiment, the temperature of the laser quenching can be 1050, 1100, 1150, 1200 or 1250°C.
[0029] In the present invention, the spot type of the laser quenching is preferably flat-top light, the spot length is preferably 10-12 mm, specifically 10, 10.5, 11, 11.5 or 12 mm; the spot width is preferably 3.5-4.5 mm, specifically 3.5, 4.0 or 4.5 mm.
[0030] In the present invention, the scanning rate of the laser quenching is preferably 8-10 mm / s. In a specific embodiment, the scanning rate of the laser quenching can be 8, 9 or 10 mm / s.
[0031] In the present invention, during the laser quenching, a cooling water flow is used to cool the area scanned by the laser, and the distance between the cooling water flow and the light spot is preferably 20 to 30 mm, specifically 20, 25 or 30 mm.
[0032] In the present invention, after each laser quenching is completed, the obtained sample is preferably placed in cold water until the sample temperature drops to room temperature before the next laser quenching is performed.
[0033] The present invention uses laser quenching to perform surface treatment on the medium-temperature aged 60NiTi alloy to construct a gradient structure. The interior is mainly composed of TiNi phase and Ni3Ti phase, maintaining the good superelasticity of the alloy to withstand high stress overload impact, while the surface layer is mainly composed of Ni4Ti3 phase and TiNi phase to obtain high hardness and high wear resistance, thereby obtaining an ultra-high hardness layer on the surface while maintaining superelasticity, achieving a good combination of high wear resistance of the alloy surface and high stress impact resistance of the alloy core.
[0034] The present invention provides a high-hardness and high-wear-resistant 60NiTi alloy, which is obtained by the method described in the above scheme; the hardness of the high-hardness and high-wear-resistant 60NiTi alloy decreases from the surface to the core; the interior is mainly composed of TiNi phase and Ni3Ti phase, and the surface is mainly composed of Ni4Ti3 phase and TiNi phase.
[0035] In the present invention, when the temperature of the laser quenching is 1050-1100°C, the surface of the high-hardness and high-wear-resistant 60NiTi alloy is composed of NiTi phase, Ni3Ti and Ni4Ti3; when the temperature of the laser quenching is 1150-1250°C, the surface of the high-hardness and high-wear-resistant 60NiTi alloy is composed of NiTi phase, Ni4Ti3 and NiTi compound. Since the temperature diffuses into the interior of the sample and NiTi is a poor conductor of heat, when the laser quenching temperature is 1050-1100°C, it is not enough to dissolve Ni3Ti but promotes the formation of Ni3Ti phase. As the temperature continues to rise, it enters the single-phase region, and the rapid laser quenching promotes the rapid nucleation of nano-scale Ni4Ti3. A large amount of Ni4Ti3 is generated in the sample to strengthen the surface.
[0036] In the present invention, the surface hardness of the high-hardness and high-wear-resistant 60NiTi alloy is preferably 400-650Hv, and in the embodiments of the present invention, it is specifically 428.79Hv, 525.49Hv, 624.29Hv, 551.87Hv or 534.15Hv. The average friction coefficient of the high-hardness and high-wear-resistant 60NiTi alloy is preferably 0.39-0.62, and in the embodiments of the present invention, it is specifically 0.62, 0.52, 0.47, 0.39 or 0.42.
[0037] Compared with the hardness (275.78Hv) and average friction coefficient (0.96) before laser quenching, the surface hardness of the 60NiTi alloy in the present invention is greatly improved and the average friction coefficient is significantly reduced after laser quenching, indicating that laser quenching significantly improves the surface hardness and friction performance of the 60NiTi alloy.
[0038] The method of inducing high hardness and high wear resistance gradient structure 60NiTi alloy by laser quenching provided by the present invention is described in detail below in conjunction with the embodiments, but they should not be understood as limiting the scope of protection of the present invention.
[0039] Example 1
[0040] Nickel with a purity of 99.96% and titanium with a purity of 99.8% were selected as raw materials for alloy preparation. The surface of the metal raw materials was polished to remove the surface oxide scale, ultrasonically cleaned, and placed in a drying oven for drying. Titanium and nickel metals were weighed according to the mass percentage using an electronic balance for standby use. The alloy was smelted in a vacuum suspension furnace. The metal raw materials were placed in the melting crucible in the furnace in order from the lowest melting point to the highest melting point, and the sample chamber was evacuated to 5×10 -2Pa is filled with high-purity argon for protection; the temperature is raised to 1500℃ and then melted, smelted for 15min and then refined for 5min, the power is adjusted to cool down, and the smelting is repeated for 3 times, and the smelted 60NiTi alloy ingot is cast and cooled in the furnace to obtain the smelted 60NiTi alloy ingot; the 60NiTi alloy ingot is kept at 850℃ in a muffle furnace for 4h and cooled with the furnace; the ingot is cut into 100×100×10mm by wire cutting; the hot melting zone and the surface oxide scale of the wire cutting are polished to remove the hot melting zone and the surface oxide scale of the wire cutting to obtain the 60NiTi matrix sample after medium temperature aging;
[0041] The 60NiTi matrix sample that has been aged at medium temperature is laser quenched: the equipment simulation diagram is as follows Figure 1 As shown;
[0042] Set the spot type to flat top light, adjust the spot length to 12mm, and the spot width to 4mm; control the laser scanning rate at 10mm / s; the laser quenching temperature is 1050℃, set the temperature error range to ±10℃, and control the room temperature at 16-25℃. The laser path is set to 120mm, and the starting and ending points of the laser path are both set on the stainless steel sample table; the cooling water flow is 20-30mm away from the laser spot to prevent the cooling water from splashing onto the spot, causing the spot temperature to drop, which will feedback to the system and cause the system temperature to be unstable, affecting the laser quenching effect; after one laser is fired, put the sample into cold water until the sample temperature drops to room temperature before the next laser quenching.
[0043] Embodiments 2 to 5
[0044] The only difference from Example 1 is that the laser quenching temperature is changed, and the laser quenching temperatures are 1100° C., 1150° C., 1200° C., and 1250° C. respectively.
[0045] Structural characterization:
[0046] Figure 2 This is a sample picture of 60NiTi alloy after laser quenching. Figure 2 It can be seen that with the increase of temperature, the width of the single track gradually increases, the degree of surface oxidation gradually increases, and micro-melting occurs at 1250℃, accompanied by slight peeling.
[0047] The high hardness and good wear resistance of 60NiTi after high-temperature solution quenching are due to the presence of the internal hard phase Ni4Ti3. The Ni3Ti phase dissolves back, and the nano-scale Ni4Ti3 phase rapidly nucleates during the quenching process. The driving force for the precipitation and growth of the Ni4Ti3 phase comes from the free energy difference between the supersaturated NiTi matrix phase and the NiTi matrix containing the Ni4Ti3 phase. The nano-scale Ni4Ti3 phase acts as a strengthening particle, evenly distributed in the NiTi matrix, playing a role of dispersion strengthening. The oxide scale on the surface of the sample was polished off with sandpaper, and the phase composition was tested using XRD. The results are as follows: Figure 3As shown, (a) is a 60NiTi substrate aged at medium temperature, that is, a substrate (core) without laser quenching. Figure 3 As shown in (a), the matrix (core) sample without laser quenching is mainly composed of NiTi phase and Ni3Ti. After laser quenching at different temperatures, the phase composition of the sample is as follows: Figure 3 As shown in (b), the samples at 1050℃ and 1100℃ are composed of NiTi phase, Ni3Ti and Ni4Ti3. When the laser quenching temperature is 1150-1250℃, the samples are composed of NiTi phase, Ni4Ti3 and NiTi compound. As the temperature diffuses into the sample and NiTi is a poor conductor of heat, the surface layer after the oxide scale is removed actually receives less than the set temperature. The samples at 1050℃ and 1100℃ are not in the single-phase region, which is insufficient to dissolve Ni3Ti and promotes the formation of Ni3Ti phase. As the temperature continues to rise, it enters the single-phase region. Laser rapid quenching promotes the rapid nucleation of nano-sized Ni4Ti3, and a large amount of Ni4Ti3 is generated in the sample to strengthen the surface.
[0048] Use sandpaper to grind off the surface oxide scale and test the Vickers hardness of the surface. Randomly measure five points on the same sample and calculate the average value. The results are as follows: Figure 4 As shown. The Vickers hardness of the 60NiTi matrix sample after medium temperature aging is 275.78Hv. After laser quenching at 1050℃, 1100℃, 1150℃, 1200℃, and 1250℃, the Vickers hardness of the sample surface is 428.79Hv, 525.49Hv, 624.29Hv, 551.87Hv, and 534.15Hv, respectively. It is worth noting that at 1150℃, the Vickers hardness is 2.30 times higher than that of the core (matrix), which is close to the effect of high temperature quenching.
[0049] A piece of sample was cut along the cross section using wire cutting. The sample was processed from coarse grinding to fine grinding to polishing. Then, alcohol ultrasound was used to test the cross section hardness using Vickers microhardness. The load used in the experiment was 1.96N and the loading time was 10s. Starting from 50μm, the cross section of the surface treatment layer was tested every 50μm. Each depth was tested 3 times on the left, middle and right sides to take the average value. The Vickers hardness results of the cross section of the laser quenched samples at different temperatures are shown in Figure 1. Figure 5 As shown in the figure. The sample after laser quenching shows an obvious gradient structure. At 50μm from the interface, as the laser temperature increases, the hardness gradually increases. The average hardness of the sample at 1250℃ is 587.19Hv, which is 2.13 times that of the core (matrix) sample. Overall, the hardness decreases gradually along the depth direction and gradually approaches the core hardness. As the temperature increases, the depth of the hardened layer gradually increases. At 1250℃, the hardened layer is about 300μm.
[0050] The laser quenched samples were cut into 10×10×10mm pieces using wire cutting and friction and wear tests were performed on a wear tester. The friction pair was a Φ6mm steel ball, the load was 5N, the speed was 200rpm, the friction radius was 2mm, and the friction time was 60min. The test results are shown in Figure 2. Figure 6 As shown. It can be observed from the figure that the friction fluctuation of the sample treated with laser quenching is significantly smaller than that of the matrix (core) sample, and the higher the temperature, the smaller the friction fluctuation. The average value of the friction coefficient of the matrix is 0.96, and the average values of the friction coefficient of the samples after laser quenching at 1050℃, 1100℃, 1150℃, 1200℃, and 1250℃ are 0.62, 0.52, 0.47, 0.39, and 0.42, respectively, indicating that laser quenching can significantly improve the friction and wear properties of 60NiTi alloy.
[0051] The 60NiTi matrix samples were subjected to high temperature quenching and medium temperature aging treatments. The high temperature quenching was performed at 1050°C, kept at this temperature for 4 hours, and then taken out for water quenching. The medium temperature aging was performed at 850°C, kept at this temperature for 4 hours, and then furnace cooled. The 60NiTi samples subjected to high temperature quenching and medium temperature aging were processed into I-shaped parts, and the superelastic stress-strain curve test was performed on an electronic universal testing machine. Figure 7 As shown in the figure, at room temperature and after 30 cycles, the sample quenched at high temperature exhibited metal-like recovery, while the sample aged at medium temperature exhibited obvious linear superelasticity after 30 cycles, with a superelastic strain of about 2%, indicating that the matrix sample treated with medium temperature aging has superelasticity, while the sample quenched at high temperature after laser quenching only exhibited high hardness and high wear resistance, and did not have superelasticity. Therefore, laser quenching can construct a gradient structure 60NiTi alloy with high hardness and high wear resistance on the surface and superelasticity in the alloy core.
[0052] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for inducing a high-hardness and high-wear-resistant gradient structure of 60NiTi alloy by laser quenching. The following steps are involved: The surface of 60NiTi alloy after medium temperature aging treatment was laser quenched.
2. The method according to claim 1, It is characterized in that The temperature of the medium-temperature aging treatment is 800-900° C., and the insulation time is 3-4 hours.
3. The method according to claim 1, It is characterized in that The temperature of the laser quenching is 1000-1300°C.
4. The method according to claim 1 or 3, It is characterized in that The temperature of the laser quenching is 1150-1250°C.
5. The method according to claim 1, It is characterized in that The light spot type of the laser quenching is flat top light, the light spot length is 10-12 mm, and the light spot width is 3.5-4.5 mm.
6. The method according to claim 1, It is characterized in that The scanning rate of the laser quenching is 8-10 mm / s.
7. The method according to claim 1, It is characterized in that During the laser quenching, a cooling water flow is used to cool the area scanned by the laser, and the cooling water flow is 20 to 30 mm away from the light spot.
8. The method according to claim 1, It is characterized in that After each laser quenching, the sample was placed in cold water until the sample temperature dropped to room temperature before the next laser quenching was performed.
9. A high-hardness and high-wear-resistant 60NiTi alloy obtained by the method according to any one of claims 1 to 8; the hardness of the high-hardness and high-wear-resistant 60NiTi alloy decreases from the surface to the core; the interior is composed of TiNi phase and Ni 3 Ti phase is dominant, and Ni 4 Ti 3 Phase and TiNi phase are the main ones.
10. The high-hardness and high-wear-resistant 60NiTi alloy according to claim 9, It is characterized in that The surface hardness is 400~650Hv, and the average friction coefficient is 0.39~0.62.
Citation Information
Patent Citations
Novel high-hardness nickel-titanium-based alloy
CN107523719A
Self-lubricating bearing with self-adaption characteristic and preparation method of self-lubricating bearing
CN108411160A
Laser quenching and aging treatment composite strengthening method for steam turbine blade surface
CN108977626A
Preparation method of GH4169 nickel-based alloy with high strength and good elongation percentage
CN116083829A
Laser quenching process parameter testing method
CN116990172A
Cited By
Preparation method of high-hardness high-wear-resistance gradient structure NM500 wear-resistant steel and wear-resistant steel
CN121065437A
